تطوير نموذج قبول التكنولوجيا واختباره على استخدام نظم المعلومات المحاسبية (دراسة تجريبية على عينة من المستخدمين في شركات النسيج في سورية) - الطويل, ليلى (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يعتبر "نموذج قبول التكنولوجيا"، الذي ابتُكر عام 1986، النموذج النظري الأكثر انتشارا وتطبيقا في مجال نظم المعلومات. وقد تم ابتكاره من قبل Davis الذي افترض فيه أن قبول نظم المعلومات من قبل الأفراد يتحدد بمتغيرين رئيسين: المنفعة المدركة، وسهولة الاستخدام المدركة، وأن هذين المتغيرين يتأثران بعوامل عدة خارجية. وتسعى هذه الدراسة الى توسيع النموذج من خلال اقتراح مجموعة متغيرات خارجية يمكن أن تؤثر على كل من المنفعة المدركة وسهولة الاستخدام المدركة. بالإضافة الى اختبار النموذج المطوّر على استخدام نظم المعلومات المحاسبية على عينة من المستخدمين في مجموعة من شركات النسيج في سورية. وتبين نتائج الدراسة أن متغير "سهولة الاستخدام المدركة" يرتبط مع الاستخدام الفعلي بشكل أقوى من ارتباط متغير "المنفعة المدركة" مع الاستخدام الفعلي، مما يدلّل على أن متغير "سهولة الاستخدام المدركة" لا يسبق متغير "المنفعة المدركة"، وأن تأثيره أقوى على الاستخدام الفعلي على نقيض ما ورد في الدراسات السابقة. يضاف إلى ذلك أن تأثير المتغيرات المستقلة المقترحة (باستثناء متغير العمر) على متغير "سهولة الاستخدام المدركة" أقوى من تأثيرها على متغير "المنفعة المدركة". وأخيراً تتأثر المنفعة المدركة بسهولة الاستخدام المدركة وتؤثر بها، مما يستدعي وضع السهم في النموذج باتجاهين. The "Technology Acceptance Model" (TAM), introduced in 1986, continues to be the most widely applied theoretical model in the information system's field. It is originally proposed by Davis (1986), and assumes that an individual's information systems, acceptance is determined by two major variables: perceived usefulness and perceived ease of use, while these two variables are influenced by external factors. This research extends the TAM model by introducing some external variables that probably influence the perceived usefulness and the perceived ease of use. The extended model is used to test the users' usage of accounting information systems on a sample of users within Syrian textile companies. The research results indicate that the "perceived ease of use" has a stronger association with the actual use than the "perceived usefulness". It can be included that the "ease of use" has not precedence over the "perceived usefulness" on the contrary with previous studies. Furthermore, the influence of the proposed independent variables (except for the "age" variable") is stronger on the "ease of use" than the "perceived usefulness". Finally, both of "ease of use" and "perceived usefulness" influence each other; that is why the arrow should be depicted to have both sides in the model.